Enhanced removal of the crystal violet dye from aqueous medium using tripolyphosphate–functionalized Zn–substituted magnetite nanoparticles - Lotfi Ben Tahar; Roaa Mogharbel; Yasmeen Hameed; Adel Noubigh; Mustafa Jaip Allah Abd Elmageed Abualreish; Ahmed Hamad Alanazi; Mohammad Rafe Hatshan (Results in Chemistry, 2025)
The efficiency of adsorptive removal of the crystal violet dye (CV) onto a Zn–substituted magnetite, Zn0.3Fe2.7O4 (Zn–Magn) nanoparticles and their corresponding sodium tripolyphosphate–functionalized nanoparticles (Zn–Magn@STPP) was investigated in details. The pristine nanoparticles (Zn–Magn) were prepared by the classical coprecipitation method, while the Zn–Magn@STPP ones were obtained by reacting colloid of the former nanoparticles with a STPP solution in an acidic pH. The produced powders consisted of single crystals of spinel–type ferrite ultrasmall (∼10 nm) almost spherical magnetic nanoparticles. Additionally, the Zn–Magn@STPP showed a robust-dense anchoring of STPP moieties onto the nanoparticles' surface. Regarding the adsorption properties, the effect of various influencing parameters on CV removal was elucidated. A clear enhancement of Zn–Magn@STPP nanoparticles for the removal of CV over the uncapped nanoparticles was evidenced. Preliminary results showed that pH is the most important factor that controls the dye adsorption and the optimum removal efficiency was determined for the natural pH (pH ∼7). Further, the adsorption process was very fast reaching an equilibrium in 15 min. Additionally, modeling of the adsorption kinetics data showed that the third order Ritchie (R3) model kinetics mechanism prevails and that the overall rate of the dye adsorption onto Zn–Magn@STPP appeared to be controlled by the chemisorption process. The last result correlates the multilayer adsorption model (corrected BET model) retained in the adsorption isothermal studies. Adsorption involved a chemisorbed monolayer enveloped by a multilayered framework of physisorbed CV moieties. Furthermore, thermodynamic studies indicated that the adsorption was feasible, spontaneous and endothermic. The desorption study demonstrated that the Zn–Magn@STPP could be readily regenerated using 0.1 M acetic acid. Moreover, adsorption-desorption studies indicated that the nanoadsorbent had an excellent regeneration–reusability capability.